Bone taphonomy inside and out: Application of 3-dimensional microscopy, scanning electron microscopy and micro-computed tomography to the study of humanly modified faunal assemblages. (20th May 2019) - Bello, Silvia M.; Galway-Witham, Julia
Abstract: Cut marks, scrape marks, knapping marks, percussion damage and engravings are examples of humanly produced modifications made on the surface of bones, antlers and/or teeth during defleshing, disarticulation, filleting, surface cleaning or when modifying these organic materials into objects and tools. These traces are direct indications of human activity and by studying how and why they were made, we can begin to understand a variety of past human behaviours. Consequently, over the last ten years we have observed an increase in the development of new analytical techniques to better understand the production, function, macro-, and micro-morphometric characteristics of bone modifications. In this study we present the application of multiple techniques to visualise and analyse the internal and external features of modified bone, teeth and antler. A Focus Variation Microscope (FVM), the Alicona InfiniteFocus optical surface measurement system, was used to examine the topography of surface modifications. This system produces 3-dimensional (3D) reconstructions, allowing evaluations of metric parameters (depth, width, area and volume) associated with different type of modifications. A Scanning Electron Microscope (SEM), operated in variable pressure mode, was used to capture higher resolution images for better characterisation and identification of the modifications and finer details, which are not always visible using a FVM. The extension of an SEM with Energy Dispersive X-ray (EDX) spectroscopy allowed for elemental analyses of the modified surfaces, including the recognition of exogenous elements imbedded within the modifications. Finally, micro-Computed Tomography (μCT) was performed to record how extensively a modification can affect and alter the internal structure of organic specimens. Analyses of μCT data also help to visualise gross surface morphology when obscured by other material. Together these approaches provide in-depth assessments of bone taphonomy on both the inside and the outside, furthering our understandings of ancient human behaviours.